(untitled) (Metallurgy and Foundry Engineering, 2019)
Friction stir welding (FSW) technology allows for the welding of materials that differ in their chemical compositions, microstructures, and properties. When selecting the parameters, it is necessary to analyze the structure of a weld and eliminate the defects. The use of X-ray microtomography creates the possibility of precise imaging of a joint structure – especially when it contains defects (voids). The tests were carried out on an FSW joint made with both 2017A and AlSi9Mg aluminum alloys. The macrostructure was cross-sectional, and a defect was found in the middle part of the joint and on the advancing side. We used a conventional method of observation light microscopy. Then, an analysis was performed using X-ray microtomography, which revealed the shape of the defect in 3D. Individual cross-sections were extracted, which enabled us to measure the geometric quantities. A dependence was found for the shape of the defect on the welding parameters and the variability of its construction. The usefulness of this advanced material imaging technology for the analysis of FSW welds has been confirmed.